Crusader for democracy : the political life of William Allen White - Delgadillo, Charles (University Press of Kansas, 2018)
"Once upon a time, "What's the Matter with Kansas?" referred not to a Thomas Frank book but to an editorial from Emporia Gazette editor William Allen White. A lifelong Republican, White saw himself as defending the common man - "The Voice of Main Street"--Even against fellow Republicans, and built a reputation as a man with little interest in partisan games. But while he positioned himself as the voice of small-town, Midwestern common sense, he was also a savvy political operative with connections to state and national political figures from both parties. Herbert Hoover and Teddy Roosevelt visited White at his home in Emporia; FDR famously quipped that he could count on White's support "three and a half out of every four years." In the first scholarly work on White in nearly twenty years, Charles Delgadillo foregrounds the famed journalist's political relationships, revealing White as a critical, influential political figure - one who represented a brand of moderate conservatism that seems to have faded amid today's heated partisanship."--Provided by publisher